2001
DOI: 10.1515/jpm.2001.065
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of meconium aspiration syndrome in term meconium-stained babies managed at birth with selective tracheal intubation

Abstract: The delivery room management of infants born through meconium stained amniotic fluid (MSAF) remains controversial. The aim of this prospective study was to evaluate maternal and neonatal characteristics of MSAF infants and the incidence of meconium aspiration syndrome (MAS) in routine delivery room management which reserved selective intubation for depressed/asphyxiated babies. Between October 1993 and September 1997, a consecutive sample of 3745 full-term infants was analyzed. Of these, 361 were MSAF infants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…Some studies suggested that prevention of postterm pregnancy prevents severe MAS [33]. The earlier induction of labour (e.g., by 41 weeks) may prove to be beneficial for the prevention of the MAS as shown by Ross [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested that prevention of postterm pregnancy prevents severe MAS [33]. The earlier induction of labour (e.g., by 41 weeks) may prove to be beneficial for the prevention of the MAS as shown by Ross [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, identification of perinatal asphyxia remains a major endpoint of MAS prevention [33]. Guidelines of earlier fetal monitoring (e.g., by 40 WG) proved to be beneficial for the prevention of MAS [34].…”
Section: Discussionmentioning
confidence: 99%
“…[107][108][109][110][111][112][113][114][115][116] Appropriate intervention to support ventilation and oxygenation should be initiated as indicated for each individual infant. This may include intubation and suction if the airway is obstructed.…”
Section: 8mentioning
confidence: 99%
“…For the critical outcome of mortality and/or MAS, we identified evidence from 9 very-low-quality observational studies [158][159][160][168][169][170][171][172][173] demonstrating no improvement in survival and/or incidence of MAS (including depressed and/or vigorous infants) when infants born through MSAF were intubated for tracheal suctioning (downgraded for indirectness).…”
Section: Perlman Et Al Part 7: Neonatal Resuscitation S219mentioning
confidence: 99%